A&T Ethiopia Maternal Nutrition Endline Survey 2021: Recently Delivered Women - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Alive & Thrive (A&T) is an initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding, and complementary feeding practices. In Ethiopia, A&T integrated a package of maternal nutrition interventions into existing ANC services delivered through government health facilities (interpersonal counseling on diet quality during pregnancy, counseling on iron-folic acid (IFA) supplementation, adequate weight-gain monitoring, counseling on early breastfeeding practices, and systems strengthening through training and supportive supervision) and community platforms (home visits, Pregnant Women Conferences/Mother Support groups, and community gatherings) that align with the latest global evidence. This dataset is part of a survey that was conducted to gather endline data for the impact evaluation of the interventions. The overall study objective was to determine the feasibility of integrating locally relevant maternal nutrition interventions into existing ANC services and determine the impact on diet quality and utilization of nutrition interventions during pregnancy. Research questions include: 1) What is the program impact on maternal practices: (1) consumption of diversified foods during pregnancy; (2) consumption of IFA supplements during pregnancy; and (3) early breastfeeding practices? 2) Can the coverage and utilization of key maternal nutrition interventions during ANC be improved through system strengthening approaches? 3) What factors influenced the integration and strengthening of maternal nutrition interventions into the government ANC service delivery platform?